UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN DARI EKSTRAK ETANOL DAUN SOYOGIK (Saurauia bracteosa DC) - Kadji, Miranty H; Runtuwene, Max R.J.; Citraningtyas, Gayatri (PHARMACON, 2013)
Soyogik (Saurauia bracteosa DC) is a plant in Actinidiaceae Families which is endemic in Indonesia, commonly found in Java and Bali. The aims of this research are to identify the active compounds and determine the antioxidant activity of the leaf extract Soyogik. Soyogik leaves extracted by maceration and soxhlet using 70% ethanol as a solvent. The tests included quantitative test of antioxidant activity by DPPH method, and phytochemical test. The results show that maceration and soxhlet extract are contained phenolic compounds, steroids, flavonoids, and saponins. Both types of extract have powerful antioxidant activity as showed on the IC50 values obtained. IC50 value of maceration and soxhlet extract are 38,01 ppm and 28,18 ppm, respectively. Key word : phytochemical test, antioxidant, Saurauia bracteosa DC.